Financial Accounting: An Integrated Approach - Trotman, Ken and Gibbins, Michael (Australia Cengage Learning, 2009)
"This is an introductory textbook for undergraduate Accounting students. It is renowned for containing a blend of both technical and end-user material."--Provided by publisher.
Includes Index
Keywords: Accounting